A study on homonymous visual field deficits using brain imaging and simulations - Beh, Anthony (2023)
Homonymous visual field deficit (HVFD) is a common and devastating complication of cerebral strokes. This impairment has a dramatic impact on quality of life, disrupting multiple facets of daily life – most notably reading fluency. At present, there are no universally accepted, effective rehabilitation programs for HVFD. The most promising strategies involve repetitive visual stimulation in the ‘blind’ field using a broad range of stimuli to perceptually “retrain” visual function. Although effectiveness of this approach varies substantially, it could be because the most appropriate areas of the field are not targeted or the stimulus used in training is not optimized for each patient. A major issue in rehabilitating HVFD is the heterogeneity across individuals, where there is variability in lesion size, location, time since lesion, and most importantly the pattern of residual visual capacity. The potential for recovery may be limited to individuals with intact cortical structures or alternative visual pathways that could support some level of visual reorganization.